Crocosphaera watsonii - A widespread nitrogen-fixing unicellular marine cyanobacterium - Masuda, Takako; Mareš, Jan; Shiozaki, Takuhei; Inomura, Keisuke; Fujiwara, Amane; Prášil, Ondřej (Journal of phycology, 2024)
Crocosphaera watsonii is a unicellular N2-fixing (diazotrophic) cyanobacterium observed in tropical and subtropical oligotrophic oceans. As a diazotroph, it can be a source of bioavailable nitrogen (N) to the microbial community in N-limited environments, and this may fuel primary production in the regions where it occurs. Crocosphaera watsonii has been the subject of intense study, both in culture and in field populations. Here, we summarize the current understanding of the phylogenetic and physiological diversity of C. watsonii, its distribution, and its ecological niche. Analysis of the relationships among the individual Crocosphaera species and related free-living and symbiotic lineages of diazotrophs based on the nifH gene have shown that the C. watsonii group holds a basal position and that its sequence is more similar to Rippkaea and Zehria than to other Crocosphaera species. This finding warrants further scrutiny to determine if the placement is related to a horizontal gene transfer event. Here, the nifH UCYN-B gene copy number from a recent synthesis effort was used as a proxy for relative C. watsonii abundance to examine patterns of C. watsonii distribution as a function of environmental factors, like iron and phosphorus concentration, and complimented with a synthesis of C. watsonii physiology. Furthermore, we have summarized the current knowledge of C. watsonii with regards to N2 fixation, photosynthesis, and quantitative modeling of physiology. Because N availability can limit primary production, C. watsonii is widely recognized for its importance to carbon and N cycling in ocean ecosystems, and we conclude this review by highlighting important topics for further research on this important species.
Keywords: sinice; Phylogeny; fylogeneze; Cyanobacteria; Nitrogen Fixation; fixace dusíku